Seguridad en trabajos de alto riesgo en altura relacionado con el conocimiento y comportamiento en los trabajadores del sector telecomunicaciones. 2023 - Chavez Marapara, Brayan Elvis (2023)
The purpose of the study is to evaluate the behavior and level of knowledge in workers in high-risk jobs at height in telecommunications. in the telecommunications services provider company MATYSGER S.A.C in the city of Lima. It is a quantitative research of the non-experimental, observational- descriptive, analytical, transversal type. The primary information was obtained through the application of a structured survey with a reliability coefficient, Cronbach’s Alpha, of 0.727. For the inferential analysis, Pearson Correlation Analysis was used. From the results obtained, the workers consider that their appropriate behavior can be essential to prevent work accidents at height, since it has medium to high influence, which is evidenced by the Pearson correlation analysis that determined that the Alternate Hypothesis is accepted, because there is a significant relationship between the level of safety knowledge and the behavior of workers in high-risk jobs at height in the company.